Development of Hollow Fiber Liquid Phase Microextraction Method for Determination of Diazinon Residues in Vegetable Samples - Eviomitta R. Amanda; Yanuardi Raharjo; Usreg S. Handajani (Jurnal Akademika Kimia, 2022)
An extraction method based on a combination of hollow fiber liquid-phase microextraction with high-performance liquid chromatography diode array detector (HF-LPME HPLC-DAD) has been developed and demonstrated to analyze pesticide residues in vegetables. This study aims to determine the optimum extraction conditions and validation performance of this method. Diazinon pesticide was selected as the target model analyte. HF-LPME is performed by stacking microliter organic solvent droplets through an HPLC syringe coated with polypropylene hollow fiber by directly dipping it into the sample solution and stirring it during the extraction process. Finally, the organic solvent was put into an HPLC syringe at the end of the extraction. Then, it was injected into the HPLC-DAD at the wavelength of 247 nm. Several important extraction parameters have been optimized. The optimization results showed the type of organic solvent of n-hexane, the length of the hollow fiber of 1.5 cm, the volume of the sample solution of 20 mL, and the stirring speed of 600 rpm. The validation performance obtained a limit of detection (LoD) of 0.10 mgL-1, limit of quantification (LoQ) of 0.33 mgL-1, percent recoveries of 99.88%, a coefficient of variation of 3% (n=15), and the enrichment factor of 19,982 times. Under optimal conditions, the developed method was applied to extract diazinon in vegetable matrix samples using the spiking method. Mustard green was selected as a model matrix sample. From the research, the percentage recoveries of diazinon obtained in the mustard green matrix sample are 98.80% - 100.41%.